Handbook of hydrothermal technology : a technology for crystal growth and materials processing - Byrappa, K. (Materials science and process technology series. Ceramic and other materials., 2001)
The Handbook explains how aqueous solvents or mineralizers work under temperature and pressure to dissolve and recrystallize normally insoluble materials, and decompose or recycle any waste material. The result, the authors suggest, is technologically the most efficient method in crystal growth, materials processing, and waste treatment.